FORMATION OF SIMPLE SENTENCE PARADIGMS WITH THE HELP OF SEMANTICS INTENSIFICATION/DEINTENSIFICATION IN THE UZBEK LANGUAGE - Ziyaev Avazjon (Galaxy International Interdisciplinary Research Journal, 2022)
This article touches upon forming new words and expressions with the help of the philosophical law “transition from quantity to quality” which is the semantic way of forming new words and simple sentences what can be called gradual way of forming new words and simple sentences.